Why do fans attend football games? Motivational factors in the ethiopian Premier League, 2023-24 - Daniel Getnet; Zelalem Melkamu; Sisay Mengistu (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Why do fans attend soccer games: investigating motivating factors for attending Ethiopian Premier League soccer games in 2023/24 G.C. A co-relational study was conducted. Sixteen seven-point linker Amharic version questionnaires, known for their validity and reliability, were used from a sample of 524 participants selected through the available sampling method. Frequency, percentage, correlation, and multiple linear regression analyses (with a significance level of P < 0.05) were performed. There was a positive correlation between the fan motivation factors and game attendance: socialization (r = 524, .669, p <.001); performance r = (524), .763, p <.001; excitement r = (524), .676, p <.001; esteem r = (524), .619, p <.001; and diversion r = (524), .630, p <.001, respectively. Furthermore, the analysis revealed that the five predictors collectively explained 69.3% of the variance in game attendance (5, 523) = 237.287, p<.001). Individual predictor analysis indicated that performance (β = .631, t = 15.200, p < .001), excitement (β = .588, t = 12.660, p < .001), and diversion (β = .333, t = 7.749, p < .001) have a positive impact on game attendance. On the other hand, socialization (β = -.382, t = -4.836, p < .001) and esteem (β = -.222, t = -3.534, p < .001) negatively affected game attendance. In conclusion, a notable positive correlation exists between fan motivation and game attendance, highlighting the importance of understanding fan motivation to increase attendance at sporting events.